Extreme dilatation of the interposed jejunal pouch after proximal gastrectomy associated with portal venous gas: A case report. (2017) - Takahashi, Michinaga; Goto, Shinji; Ueno, Tatsuya; Shima, Kentaro; Inoue, Koetsu; Douchi, Daisuke; Nishina, Orie; Naito, Hiroo
Highlights: Dilatation of the interposed jejunal pouch developed after proximal gastrectomy. Shock state with portal venous gas was restored after conservative therapy. The pouch dilatation recurred soon after resuming oral ingestion. Resection of the pouch with R-Y esophagojejunostomy relieved the patient. Surgical intervention should be considered for refractory pouch dilatation. Abstract: Introduction: The jejunal pouch interposition (JPI) after proximal gastrectomy (PG) was proposed as a reconstructive procedure to provide a gastric reservoir substitute and prevent postgastrectomy syndrome. However, food residue remaining in some of the pouches resulted in the adverse effect of abdominal bloating, thereby body weight loss. Here, we report a rare case with an extreme dilation of the interposed jejunal pouch (JP) 8 years after PG, requiring pouch resection. Presentation of case: A 65-year-old-man who had undergone PG with an inverted U-shaped JPI for early gastric cancer 8 years previously, suffered from shock after right hip joint implantation. Abdominal enhanced CT scan revealed an extremely dilated JP accompanied by portal venous gas. After 5 months of conservative therapy, he underwent resection of the JP and gastric remnant with Roux-en-Y esophagojejunostomy reconstruction. After the operation, the patient has remained in good health for over 3 years. Discussion and conclusion: Long-term operative outcome following pouch operation for gastric cancer still remains controversial. Surgical intervention should be considered when we encounter patients who have refractory pouch dilatation after surgery for gastric cancer.